Urinary and fecal continence in adolescent and adult patients with cloacal exstrophy: urological congenitalism - Wenk, Maren; Mühlbauer, Julia; Schwarzer, Nicole; Stein, Raimund; Younsi, Nina (Urology, 2022)
Objective - To evaluate the prevalence of urinary (UI) and fecal incontinence (FI) and the incontinence-related quality of life (QoL) in adolescent and adult patients with cloacal exstrophy (CE) in Germany. - Patients and Methods - CE-patients of a tertiary care center and the German support group for anorectal malformations (SoMA e.V.) were included (October 2015 until September 2020). Data were assessed using a composed questionnaire consisting of 18 self-generated questions and two validated German questionnaires (King's health questionnaire, Questionnaire on Quality of Life in Fecal Incontinence (FLQAI)). - Results - Out of 23 included patients, 19 had continent and 3 incontinent urinary diversions (UD), 1 was unspecified; 2/23 were on dialysis. 73.7% (14/19) had undergone bladder augmentation, 4/19 had a pouch, 1/19 a neobladder. 94.7% (18/19) had a continent cutaneous channel and performed intermittent self-catheterization. UI was common (71.4%, 15/21). Neither the UD nor the involuntary loss of urine itself had a significant impact on QoL. Comparing the King's health questionnaire results, UI-related QoL of CE-patients was significantly lower than in a published reference group. 78.3% (18/23) had a bowel stoma. 34.8% (8/23) reported involuntary stool-soiling. Neither the way of bowel-emptying nor involuntary stool-soiling itself showed significant influence on FI-related QoL in the FLQAI. FLQAI items showed significant differences only for one of two published reference groups. - Conclusion - Long-term incontinence rates in adolescent and adult CE-patients are high. Incontinence-related QoL was reduced compared to published reference groups but was minimally influenced by incontinence itself, the type of UD or the way of bowel-emptying, respectively.
Online verfügbar: 14 January 2022, Artikelversion: 13 June 2022
Gesehen am 16.01.2024